2008
DOI: 10.1136/gut.2007.142588
|View full text |Cite
|
Sign up to set email alerts
|

Reduced  -defensin expression is associated with inflammation and not NOD2 mutation status in ileal Crohn's disease

Abstract: Background and aims: Reduced ileal Paneth cell adefensin expression has been reported to be associated with Crohn's disease, especially in patients carrying NOD2 mutations. The aim of this study was to independently assess whether NOD2, a-defensins and Crohn's disease are linked. Methods: Using quantitative real-time polymerase chain reaction (RT-PCR), we measured the mRNA expression levels of key Paneth cell antimicrobial peptides (DEFA5, DEFA6, LYZ, PLA2G2A), inflammatory cytokines [interkelukin 6 (IL6) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
163
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 36 publications
12
163
1
1
Order By: Relevance
“…For the regulation of hBD-2 a role of NOD2 has been reported, 47 but for other AMPs only few data exist. 48 The observed regulation of the mRNA of AMPs, cytokines and PRR suggested the involvement of bacteria in the pathogenesis of appendicitis. To assess these microbial communities associated with appendicitis we applied phylogenetic taxonomy based on 16S rDNA sequencing and observed an overall decrease in richness and diversity of the microbial flora in the inflamed appendices that was especially visible in low abundance bacterial taxa.…”
Section: Discussionmentioning
confidence: 99%
“…For the regulation of hBD-2 a role of NOD2 has been reported, 47 but for other AMPs only few data exist. 48 The observed regulation of the mRNA of AMPs, cytokines and PRR suggested the involvement of bacteria in the pathogenesis of appendicitis. To assess these microbial communities associated with appendicitis we applied phylogenetic taxonomy based on 16S rDNA sequencing and observed an overall decrease in richness and diversity of the microbial flora in the inflamed appendices that was especially visible in low abundance bacterial taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in villin expression are linked with several GI disorders associated with abnormal apoptosis. 30 Gelsolin levels are elevated in many senescent tissues where increased gelsolin expression is believed to be responsible for the resistance to apoptosis and to the increased susceptibility of these tissue to cancer. 31 Studies done in yeast have shown that actin functions as a sensor that links changes in the nutritional status with mitochondrial-dependent commitment to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Nod2 mutations associated with Crohn's disease primarily predispose the development of ileal lesions (18) corresponding to the location of Paneth cells. Ileal Crohn's disease is characterized by a decrease in antimicrobial ␣-defensins produced by Paneth cells (19,20). Studies comparing ␣-defensin levels in ileal Crohn's patients who did not have Nod2 mutation and in those who had any of the 3 major mutations (R702W, G908R, and 1007fs) associated with Crohn's disease showed no significant difference in ␣-defensin levels between the 2 groups (20).…”
mentioning
confidence: 99%
“…Ileal Crohn's disease is characterized by a decrease in antimicrobial ␣-defensins produced by Paneth cells (19,20). Studies comparing ␣-defensin levels in ileal Crohn's patients who did not have Nod2 mutation and in those who had any of the 3 major mutations (R702W, G908R, and 1007fs) associated with Crohn's disease showed no significant difference in ␣-defensin levels between the 2 groups (20). However, studies of individual mutations in Nod2 showed that the 1007fs mutation in Nod2 causes a decrease in the expression of ␣-defensin (19,21).…”
mentioning
confidence: 99%